Superfluidity of 4He confined in nanoporous media: Жидкий гелий - Shirahama, Keiya; Yamamoto, Keiichi; Shibayama, Yoshiyuki (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We have examined superfluid properties of 4He confined to a nanoporous Gelsil glass that has nanopores2.5 nm in diameter. The pressure–temperature phase diagram was determined by torsional oscillator, heatcapacity and pressure studies. The superfluid transition temperature Tc approaches zero at 3.4 MPa, indicating a novel quantum superfluid transition. By heat capacity measurements, the nonsuperfluid phase adjacent to the superfluid and solid phases is identified to be a nanometer-scale, localized Bose condensation state, in which global phase coherence is destroyed. At high pressures, the superfluid density has a T-linear term, and Tc is proportional to the zero-temperature superfluid density. These results strongly suggest that phase fluctuations in the superfluid order parameter play a dominant role on the phase diagram and superfluid properties.